Once was not enough: A case report of the concomitant intoxication of amlodipine (calcium channel blocker) and clonazepam (benzodiazepine). Issue 7 (11th July 2022) - Gautam, Swotantra; Chamlagain, Mandita; Yadav, Gopal Kumar; Acharya, Santosh
Abstract: We report a case of concurrent ingestion of Clonazepam and Amlodipine in a 25‐year‐old man, in a second attempt to take his life, which resulted in unconsciousness, hypotension, and hypokalemia. The clinical and/or biochemical presentation varied from the individual pattern when ingested. In the scarcity of consensus recommendations, supportive treatment helped. Abstract : Supportive treatment is the rule of management of concomitant ingestion of Amlodipine and Clonazepam. The clinical and/or biochemical presentation of benzodiazepine and calcium channel blocker may vary from the individual pattern.